2014
DOI: 10.3133/sir20145162
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic conditions in urban Miami-Dade County, Florida, and the effect of groundwater pumpage and increased sea level on canal leakage and regional groundwater flow

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Increasing population can result in larger demand for groundwater, especially in arid regions. Groundwater extraction may lead to reductions in freshwater discharge to the coast, and these groundwater withdrawals can affect fresh SGD (Mazi et al, 2013;McCormack et al, 2014;Michael et al, 2013) as well as groundwater discharge to inland water bodies (Hughes & White, 2014). Ferguson and Gleeson (2012) showed that the threat of saltwater intrusion in coastal aquifers is more influenced by groundwater extraction than sea level rise.…”
Section: Opportunities For Global Analysismentioning
confidence: 99%
“…Increasing population can result in larger demand for groundwater, especially in arid regions. Groundwater extraction may lead to reductions in freshwater discharge to the coast, and these groundwater withdrawals can affect fresh SGD (Mazi et al, 2013;McCormack et al, 2014;Michael et al, 2013) as well as groundwater discharge to inland water bodies (Hughes & White, 2014). Ferguson and Gleeson (2012) showed that the threat of saltwater intrusion in coastal aquifers is more influenced by groundwater extraction than sea level rise.…”
Section: Opportunities For Global Analysismentioning
confidence: 99%
“…Conceptually, leakage from the canal system can recharge the groundwater aquifer when surface-water stages are maintained at higher levels than groundwater levels or can discharge water coastward from the aquifer when groundwater levels are higher than surface-water stages. A recent hydrologic study in adjacent Miami-Dade County indicates that the surface-water system discharges more water from the aquifer than it recharges to the aquifer (Hughes and White, 2014). The directionality of these groundwater/surface-water interactions depend upon seasonal conditions and water management practices.…”
Section: Canal Systemmentioning
confidence: 99%
“…Fresh groundwater that flows toward the ocean or other coastal features, such as Barnegat Bay, mixes with seawater and forms a transition zone. The size and location of the transition zone depends on aquifer properties and groundwater flow in the area of the transition zone (Hughes and White, 2014).…”
Section: Simulation Of Freshwater-seawater Interfacementioning
confidence: 99%